2004
DOI: 10.1097/00045391-200401000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Myocardial Vulnerability by Atrial Fibrillation

Abstract: Certain groups are known to have an increased risk for sudden cardiac death. Epidemiologic studies have suggested that patients with atrial fibrillation may be at higher risk. The authors hypothesize that atrial fibrillation may increase myocardial vulnerability. To test this hypothesis, 37 dogs were studied using programmed electrical stimulation techniques to determine myocardial vulnerability as assessed by the ability to provoke ventricular tachycardia. Prior to atrial fibrillation, programmed electrical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Somberg et al reported that VT was induced in 25 of 26 dogs by programmed electrical stimulation of the ventricle only during AF, and not in sinus rhythm. 33 As discussed earlier, analysis of device-stored electrograms has revealed a higher incidence of short-long-short cycles preceding ventricular arrhythmias in AF compared with patients in sinus rhythm (50% vs. 16%, P=0.002). 19 Collectively, these observations suggest that atrial tachyarrhythmias may increase susceptibility to ventricular tachyarrhythmias.…”
Section: Possible Mechanisms Underlying the Association Of Af With Scdmentioning
confidence: 73%
“…Somberg et al reported that VT was induced in 25 of 26 dogs by programmed electrical stimulation of the ventricle only during AF, and not in sinus rhythm. 33 As discussed earlier, analysis of device-stored electrograms has revealed a higher incidence of short-long-short cycles preceding ventricular arrhythmias in AF compared with patients in sinus rhythm (50% vs. 16%, P=0.002). 19 Collectively, these observations suggest that atrial tachyarrhythmias may increase susceptibility to ventricular tachyarrhythmias.…”
Section: Possible Mechanisms Underlying the Association Of Af With Scdmentioning
confidence: 73%
“…Previous studies have observed that atrial fibrillation increases the risk of SCD in patients with heart failure, prior myocardial infarction, and even in general population . Experimental studies also support the concept that atrial fibrillation can facilitate the induction of ventricular tachyarrhythmia, which may be the cause of the association of atrial fibrillation with a higher incidence of SCD …”
Section: Discussionmentioning
confidence: 99%
“…reported from canine experiments that ventricular tachycardia (VT) was induced in 25 of 26 dogs by programmed electrical stimulation only in AF, and not in sinus rhythm. 25 Gronefeld et al . reported that AF is an independent predictor of implantable cardioverter-defibrillator therapy for VT or ventricular fibrillation (VF).…”
Section: Commentmentioning
confidence: 99%